An existential-phenomenological explication of the older person's perception of anticipated death - du Plessis, Christine Edna (Rhodes University, Faculty of Humanities, Department of Psychology, 1988)
This study attempts to explore, both theoretically and empirically, death anxiety across the lifespan in Western society. Six elderly women between the ages of 75 and 90 years were interviewed about their current perceptions and attitudes toward their anticipated deaths, and to what extent these perceptions may have altered over the course of the life cycle. It was hypothesized that an acceptance of religion and a belief in an afterlife existence; a sense of having experienced death before, in seeing loved ones die; and a feeling of having lived a meaningful life through the reminiscence of past events would all facilitate an older person's acceptance of anticipated death. An existential phenomenological explication of the protocols revealed that: religion need not necessarily play a major role in this regard; both the life reminiscence process and having experienced death before in seeing loved ones die facilitated acceptance of death; older persons are prepared for death in the sense of experiencing a feeling that their life cycles have been completed; although death may not be feared, many fears of dying are prevalent. It was thus concluded from this study that, although death is not a major preoccupation of the older person, it does still play a significant role in the lives of the elderly in that being aware of impending death allows the older person to regulate her life according to Ì•Ì•Ì•Ì•Ì•Ê¾time-left-to-liveÊ¾
Keywords: Death -- Psychological aspects